Pengaruh Parameter Rasio Liquid-Solid, Suhu Dan Lama Perawatan Terhadap Kuat Tekan Paving Blok Geopolimer - Thomson Simanjuntak; Aman Aman; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Fly ash as a substitute for cement shows potential waste utilization. The objective of the research is to find the optimum parameter to produce geopolymer. Use of fly ash type F from Paiton Probolingo power plant, fine aggregate of sand,NaOH 14M and Na2SiO3 solution. The liquid activator/solid (fly ash) ratio varies 0.3; 0.5 and 0.7 and treatment temperature variations from room temperature (30), 60, 80 and 100 oC and curing time of 3, 7, 14 and 28 days. The modulus activator ratio of Na2SiO3 / NaOH is 2 and the ratio of fly ash to aggregate is 1: 3. Compressive strength obtained 314.20 kg/cm2 at optimum ratio of liquid/solid 0.5 and curing at 80 oC and 28 days.Keywords: Fly ash; Geopolymer; Paving block; Compressive Strength; Modulus.